An Integration of Business Model Strategies for Social Enterprises in Thailand - Tangratanavalee, Aekachai; Uon, Vichit (Journal of Neonatal Surgery, 2025)
Sustainability is a crucial dimension that social enterprises need to build in both financial and social mission. There have been several systemic challenges hindering the growth of Thai social enterprises. This study aims to analyse the integration of social missions with business strategies and to propose an initial model for strategy integration for Thai social enterprises. The researchers employed a qualitative research methodology, using in-depth interviews to collect the data from 30 samples who are successful social entrepreneurs from the manufacturing and service sectors in Thailand. The results reveal five key success factors for social enterprises: 1) a clear social mission, 2) the use of innovation in solving social problems both in terms of products and processes, 3) the cross-sector collaboration, 4) the creation of social value, and 5) the impact measurement. The study proposes the strategy integration model for social enterprises in Thailand, which consists of 4 aspects: 1) creating a business brand with a clear mission, 2) expanding collaboration networks with government agencies and international organizations, 3) developing standardized social impact measurement systems, and 4) creating an exit plan and a sustainable revenue-generating business model. These insights offer practical implications for policymakers, practitioners, and stakeholders seeking to strengthen Thailand’s social enterprise ecosystem and sustainably enhance the social value.